Recomposing the Handover and Return to Parents in the Juvenile Justice System in Indonesia: Dilemma between Best Interest of the Juvenile and Legal Shadow - Wahyudi, Setya; Hendriana, Rani; Oktobrian, Dwiki; Nunna, Bhanu Prakash (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
The Indonesian Juvenile Justice System, established by Law No. 11 of 2012, focused on restorative justice and diversion strategies. However, two distinct aspects—handover and return to parents—do not possess sufficient supervisory measures, which raises doubts about their effectiveness in reducing recidivism and serving justice for victims. This article analyzes the legal framework and practical application of these elements using both normative and empirical methods, including interviews conducted with probation officers at the Purwokerto Correctional Center. The results indicate that although both approaches strive to safeguard the psychological health of child offenders, they lack enforceable responsibilities for parents or active community oversight. This results in a notable legal gap at the implementation level. The study suggests a redesign that combines the oversight of probation officers with community involvement to ensure observable behavioral improvements and accountability. This model aims to harmonize the principles of restorative justice with societal demands for fair justice and consideration for victims. The novelty of this article lies in providing a comprehensive institutional framework for post-diversion supervision, which has been mostly overlooked in earlier research.